The Renaissance & early Mondern Era 1454-1600 / Volume 2 - 20160731 frey50; Moose, Christina J., 1952-; Magill, Frank Northen, 1907- (Pasadena, Calif. : Salem Press, 1991)
Great Lives from History: This series revises the 11-volume Dictionary of World Biography. The Ancient World adds 66 new entries covering a wider geographical area and including more women, Asians, and Africans; updated bibliographies; a new page design; and a maps section. It includes 326 essays. No other comparably priced title covers the same breadth of content (geography, gender, area of achievement) with extended essays. The librarian-approved article format runs 3-6 pages, which is much more in depth than an encyclopedia entry but more accessible than a full-length scholarly treatment. Each article begins with ready-reference listings: Name by which the person is best known to English readers; Birth and death dates and places Identifier stating the person's nationality and life role; Areas of achievement list; Statement summarizing the person's contribution. Articles are then divided into four parts: Early Life: facts about the person's upbringing and the environment in which he or she was reared, as well as the pronunciation of his or her name, if unusual; Life's Work: the heart of the article consists of a straightforward account of the period during which the person's most significant achievements were made; Significance: overview of the person's place in history; Further Reading: annotated, descriptive bibliography, a starting point for further research. In addition, each essay is cross-referenced to other essays within the volume as well as to relevant essays in the companion set, Great Events from History: The Ancient World.
Leonardo da Vinci-Huldrych Zwingli, indexes.
Includes bibliographical references and index
Keywords: Biography -- 15th century; Biography -- 16th century; Renaissance